2008
DOI: 10.1089/neu.2007.0331
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Axonal Injury in the Spinal Cord Evoked by Traumatic Brain Injury

Abstract: Although it is well known that traumatic brain injury (TBI) evokes traumatic axonal injury (TAI) within the brain, TBI-induced axonal damage in the spinal cord (SC) has been less extensively investigated. Detection of such axonal injury in the spinal cord would further the complexity of TBI while also challenging some functional neurobehavioral endpoints frequently used to assess recovery in various models of TBI. To assess TAI in the spinal cord associated with TBI, we analyzed the craniocervical junction (CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 20 publications
(8 reference statements)
1
21
0
Order By: Relevance
“…The presence of TAI in the CC, internal capsule, optic tracts, cerebral and cerebellar peduncles, and the long tracts in the brainstem was consistent with previous studies that showed axonal pathology in similar locations in the original Marmarou model (Czeiter et al, 2008;Kallakuri et al, 2003;Marmarou et al, 1994;Rafols et al, 2007;Stone et al, 2001). Our results also showed that the extent of TAI was significantly greater at 2.25 m than at 1.25 m, which agrees with a preliminary study by Kallakuri and associates (2003), showing that TAI in the CC was most severe in the 2-m group, and mildest in the 1-m group.…”
Section: Traumatic Axonal Injury Quantificationsupporting
confidence: 90%
See 1 more Smart Citation
“…The presence of TAI in the CC, internal capsule, optic tracts, cerebral and cerebellar peduncles, and the long tracts in the brainstem was consistent with previous studies that showed axonal pathology in similar locations in the original Marmarou model (Czeiter et al, 2008;Kallakuri et al, 2003;Marmarou et al, 1994;Rafols et al, 2007;Stone et al, 2001). Our results also showed that the extent of TAI was significantly greater at 2.25 m than at 1.25 m, which agrees with a preliminary study by Kallakuri and associates (2003), showing that TAI in the CC was most severe in the 2-m group, and mildest in the 1-m group.…”
Section: Traumatic Axonal Injury Quantificationsupporting
confidence: 90%
“…Most previous studies assessed TAI level based on drop height (Czeiter et al, 2008;Sawauchi et al, 2004;Vagnozzi et al, 2005), but did not quantify the mechanical response of the head. Results from our current study showed that in spite of minimal variations in impactor velocity, biomechanical responses in the rat head can vary widely within the same drop height.…”
Section: Biomechanical Parametersmentioning
confidence: 99%
“…In spite of the fiber damage observed in the left thoracic CST at 4 weeks post injury, there was no evident decrease in motor performance of the left hindlimb on the horizontal ladder. However, this lack of measurable motor deficits produced by secondary damage has been reported previously (Czeiter et al, 2008;Iizuka et al, 1989). Also, in a clinical setting, spinal cord-injured patients, as well as stroke patients, usually recover gradually, although secondary tissue damage is known to occur in a delayed fashion (Ishida and Tominaga, 2002).…”
Section: Discussionmentioning
confidence: 94%
“…While there was no striking evidence for the presence of DAI, Strich came to the realization that extended degeneration of axons over a time period after the trauma was responsible for the high rate of mortality. The pathologic term DAI was established after Strich published her findings; later, it was agreed that DAI was a multipart pathology in that not only does the initial trauma cause severe damage, but also secondary factors such as biochemical cascades, edema, and hypoxia also contribute to the pathology as a whole [85,86]. It was in the early 1980s where the official term, DAI, was introduced and accepted worldwide as a pathology which played a key integral role in the posttraumatic development of the patient [87].…”
Section: The History Behind Daimentioning
confidence: 99%